FORMULASI DAN KARAKTERISASI NANOEMULGEL LIP SERUM CERAMIDE DENGAN OPTIMASI RESPONSE SURFACE METHODOLOGY - Sandry Eka Saputri Nst; Wira Noviana Suhery; Deni Anggraini (Jurnal Penelitian Farmasi Indonesia, 2026)
Lip skin possesses a thin stratum corneum (10–15 μm) with low ceramide and lipid content, rendering it particularly susceptible to dehydration and environmental damage. This study aimed to develop and characterize a ceramide nanoemulgel lip serum using Response Surface Methodology (RSM) with Simplex Lattice Design (SLD) optimization, and to evaluate its efficacy in improving lip moisture in vivo. Nanoemulsion optimization was performed using Design Expert® v.13.0, with grape seed oil (1–2%), Tween 80 (6–10%), and Kolliphor® RH40 (6–10%) as independent variables, and pH and percent transmittance as responses. The optimal formula comprised grape seed oil 1.346%, Tween 80 7.001%, and Kolliphor® RH40 9.652% (desirability 0.967). The optimized nanoemulsion was incorporated into a nanoemulgel with 0.2% Carbopol 940. Physicochemical evaluation revealed a particle size of 18.1 nm, a low polydispersity index, zeta potential of +2.0 mV, pH 5.5, and viscosity of 386.4 cP. Physical stability was maintained over 12 weeks under three storage conditions without significant change (p>0.05). Irritation testing on 5 panelists yielded negative results. The in vivo efficacy testing demonstrated a statistically significant improvement in lip moisture (p<0.001): ceramide nanoemulgel achieved 22%, compared to base lip serum (11%) and negative control (3.33%).